Kamikihito Enhances Cognitive Functions and Reward-Related Behaviors of Aged C57BL/6J Mice in an Automated Behavioral Assay System - Oizumi, Hiroaki; Miyazaki, Shinji; Tabuchi, Masahiro; Endo, Toshihiro; Omiya, Yuji; Mizoguchi, Kazushige (Frontiers in Pharmacology, 2020)
The cognitive and psychological domains of frailty in the elderly have drawn increasing attention given the aging of society. However, therapeutics to treat minor deficits in cognition and mental state in the elderly remain an unmet need. Kamikihito (KKT), a traditional Japanese Kampo medicine indicated for neuroses, anxiety, and insomnia, is effective for treating cognitive dysfunction and depressive-like behaviors in animal models, suggesting that it may have therapeutic potential for treating cognitive and/or mental frailty. In this study, we first validated the known anxiolytic effects of KKT in a conventional maze test. We then introduced an automated behavioral assay system, IntelliCage, to evaluate the therapeutic potential of KKT for age-related and diverse central functions by performing sequential behavioral tasks in young and aged mice to assess basal activities, cognitive functions, perseveration, and hedonic-related behaviors. Although young mice treated with KKT did not exhibit changes in diurnal variation, KKT-administered aged mice exhibited an accelerated decline in voluntary activity during the early part of the light period, implying that KKT may promote sleep onset in aged mice. Neither place learning acquisition for gaining rewards nor subsequent behavioral flexibility performance was altered by KKT in the young group, whereas the aged KKT group exhibited significantly enhanced performance in both phases of learning relative to age-matched controls. Conversely, perseverative nose-pokes (NPs) to gain rewards observed during place learning, indicative of compulsivity, were attenuated by KKT in both age groups. Regarding hedonic processing, aged mice exhibited a decreased preference for sweet solutions compared to young mice, which was effectively reversed by KKT treatment. Furthermore, KKT elevated high-effort choices for high-value reward in an effort-based decision-making paradigm in both age groups, implying augmentation of motivational behaviors by KKT. Collectively, KKT exerted various beneficial effects in cognitive and emotional domains, several of which were more evident in aged mice than in young mice, suggesting the potential of KKT for treating cognitive and mental frailty.